THE IMPACTS OF POLITICAL UNCERTAINTY ON THE EFFICIENCY OF COMMERCIAL BANKS: EVIDENCE FROM EMERGING ECONOMIES - Đoàn Anh Tuấn (Tạp chí Khoa học Đại học Đà Lạt)
This study examines the impacts of political uncertainty on the efficiency of commercial banks across 20 emerging economies. Using the Stochastic Frontier Approach (SFA) to measure efficiency scores of these banks during the period from 2003 to 2012, we found that political uncertainty during national elections tends to impede the banking efficiency. The results, however, did not display a statistically significant effect of political uncertainty on the efficiency around the elections  (i.e. before and after an election). In terms of the role of ownership structure, our results provided the evidence that state-owned banks tend to have lower efficiency than comparable private banks, while no difference exists in cost efficiency between foreign-owned and domestic private banks.